2023
DOI: 10.1371/journal.ppat.1011129
|View full text |Cite
|
Sign up to set email alerts
|

Haem transporter HRG-1 is essential in the barber’s pole worm and an intervention target candidate

Abstract: Parasitic roundworms (nematodes) have lost genes involved in the de novo biosynthesis of haem, but have evolved the capacity to acquire and utilise exogenous haem from host animals. However, very little is known about the processes or mechanisms underlying haem acquisition and utilisation in parasites. Here, we reveal that HRG-1 is a conserved and unique haem transporter in a broad range of parasitic nematodes of socioeconomic importance, which enables haem uptake via intestinal cells, facilitates cellular hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The parasitic L4s and adult worms need to ingest a large amount of haemoglobin in their intestine to maintain their normal development and reproduction [ 40 ], so it is no surprise that we showed the intestine as a major organ forming haemozoin-like pigments. Recently, the mechanism of haem acquisition of H. contortus has also shown that the intestine is an important organ where haem-responsive gene-1 protein (HRG-1) can facilitate haem uptake and utilisation [ 41 ]. We observed that the haemozoins in lipid droplets were located in intestinal cytoplasm, which is in line with hookworm Nippostrongylus brasiliensis [ 6 ], but different from helminth Schistosoma mansoni and insect Rhodnius prolixus [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The parasitic L4s and adult worms need to ingest a large amount of haemoglobin in their intestine to maintain their normal development and reproduction [ 40 ], so it is no surprise that we showed the intestine as a major organ forming haemozoin-like pigments. Recently, the mechanism of haem acquisition of H. contortus has also shown that the intestine is an important organ where haem-responsive gene-1 protein (HRG-1) can facilitate haem uptake and utilisation [ 41 ]. We observed that the haemozoins in lipid droplets were located in intestinal cytoplasm, which is in line with hookworm Nippostrongylus brasiliensis [ 6 ], but different from helminth Schistosoma mansoni and insect Rhodnius prolixus [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The free-living nematode C. elegans (wild-type N2 strain and mutant-type RB1515 strain) was obtained from the Caenorhabditis Genetics Center (CGC) and maintained following the manufacturer’s instructions. Parasitic nematode H. contortus (ZJ isolate) was experimentally maintained in Hu sheep and the eggs, first- (L1s), second- (L2s), third- (L3s), and fourth-stage larvae (L4s), and the adult worms were collected as described previously [ 33 , 34 ]. The human embryonic kidney 293 T (HEK 293 T) cell line (Beyotime, Shanghai) was maintained following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…HRG-5 has a histidine residue at a slightly different position within the same transmembrane domain, which might be involved in heme transport [23]. The hrg-1 orthologs in the filarial nematode Brugia malayi and barber's pole worm Haemonchus contortus, BmHRG-1 and HcHRG-1, are also regulated by heme levels [40,41]. BmHRG-1 and HcHRG-1 localize to both the cell surface and endocytic compartments, suggesting that they may have the function of both C. elegans HRG-1 and HRG-4 [40,41].…”
Section: Heme Storage and Mobilizationmentioning
confidence: 99%
“…Orthologs of hrg-1 have been identified and characterized in mammals, fish, ticks, parasitic nematodes, and trypanosomatids [23,40,41,[49][50][51][52][53][54][55]. In mammals, the vast majority of iron used for the synthesis of heme and hemoglobin in differentiating erythroblasts is supplied by tissue macrophages, which are responsible for recycling iron from senescent red blood cells (RBCs) [56,57].…”
Section: Hrg-1 Homologsmentioning
confidence: 99%